Basic helix-loop-helix (bHLH) transcription factor MdbHLH3 negatively affects the storage performance of postharvest apple fruit - Wenyan Wang; Jianqiang Yu; Mengchi Du; Jiahui Wang; Dagang Hu (Horticultural Plant Journal, 2022)
The storage period of fleshy fruits greatly affects their quality and selection, and is largely controlled by genetic factors. Therefore, it is imperative to elucidate how genetic factors affect fruit ripening and its storage. Here, we evaluated the postharvest storage properties of the basic helix-loop-helix (bHLH) transcription factor MdbHLH3-overexpressing transgenic Royal gala apple fruits. During storage, the contents of starch, malic acid, fructose, glucose, and sucrose in fruits of three MdbHLH3 transgenic lines were always higher than those of the wild-type (WT) control. Interestingly, the sugar-acid ratio also showed the same trend during fruit storage. Additionally, the fruit firmness decreased with increasing storage time, and the contents of cell wall components such as water-soluble pectin and cellulose in transgenic fruits were higher than those in control fruits, while the firmness of transgenic fruits was lower than that in WT control fruits. Though the ethylene release rate in both showed the same trend (firstly increasing, then decreasing, and finally peaking) in 90-day stored fruits, transgenic apples had higher ethylene levels than the WT control throughout storage. Furthermore, the activities of membrane peroxidase, antioxidant enzymes, and fruit ripening enzymes in all transgenic fruits were significantly higher than those in the WT control. Thus, our findings show how MdbHLH3 negatively regulates and reduces apple storage time. This may prove useful for not only developing biotechnological strategies, but also support traditional breeding programs, to help improve the storage time of fleshy fruits.